Nature & Buen Vivir in Ecuador: The battle between conservation and extraction (Alternautas, 2014)
Subjective wellbeing, economic policies, environmental protection, community, food sovereignty, Buen Vivir This post discusses a recent article published in Ecological Economics that provides a quantitative approach to assessing whether the subjective wellbeing (SWB) of Ecuadorian people is dependent on income and employment or on more distinctive features relating to Buen Vivir ethos. The latter are reflected in the indigenous Buen Vivir ideology, based mainly on relations with the community, the environment and food sovereignty. The empirical analysis shows that both Buen Vivir features and factors such as income and unemployment status are significant in the models explaining SWB. Accordingly, economic policies should take into account the Buen Vivir ethos, that seems to be important for the SWB of the Ecuadorian people. This supports the conservationist political position, which focuses on protecting the environment and people's traditional livelihoods, rather than the extractive view, which regards people's welfare as merely dependent on income.